"Just Business" – Is the Current Regulatory Framework an Adequate Solution to Human Rights Abuses by Transnational Corporations?. Issue 3 (1st May 2017) - Santoso, Benny
Abstract : Parallel to exponential proliferation and ever-increasing allegations of human rights violations by transnational corporations, the sparks produced by the friction between the normatively distinct disciplines of business and human rights have invited scrutiny across the media, academia, and industries alike. Given the fact that regulatory capacities of home and host states have evidenced an inability to keep pace with the developments, concerted efforts at the international level are imperative. By constructing its own benchmark of adequacy with reference to regulatory instruments' underlying objectives, this Article explores whether the existing regulatory framework is adequate, with a particular focus on the UN Framework and UN Guiding Principles—currently the most robust regime yet. The Article's analysis centers on (1) the terminologies utilized, (2) the human rights due diligence mechanism, and (3) access to remedies requirements, to reveal their inherent inadequacy with the hope of warning against uncritical acceptance and to inform future developments.